The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.30871/jama.v1i2.502
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Manajemen Laba, Corporate Governance, Dan Corporate Social Responsibility Terhadap Tax Avoidance

Abstract: This research aimed to present an empirical evidence influence of earnings management, corporate governance,  and corporate social responsibility disclosure on tax avoidance. Earnings management measured using model jones, corporate governance mechanism seen from institutional ownership, managerial ownership, audit commute, audit quality. Disclosure of corporate social responsibility using the global reporting initiative generation four (GRI-G4). Tax avoidance as measured by cash effective tax rate (CETR). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 3 publications
(4 reference statements)
1
2
0
16
Order By: Relevance
“…However, if a business is less aggressive in concealing its profit information, tax aggressiveness is assumed to decrease. This study's findings corroborate those of Septiadi et al (2017), who discovered a significant negative relationship between corporate tax avoidance practices or actions and earnings through concealing income.…”
Section: Discussionsupporting
confidence: 87%
“…However, if a business is less aggressive in concealing its profit information, tax aggressiveness is assumed to decrease. This study's findings corroborate those of Septiadi et al (2017), who discovered a significant negative relationship between corporate tax avoidance practices or actions and earnings through concealing income.…”
Section: Discussionsupporting
confidence: 87%
“…Following the submission of the first hypothesis, this study is in line with research (Ratnawati et al, 2018) which states that managerial ownership has a positive value of 0.003 less than 0.05, so it can be concluded that managerial ownership affects tax avoidance. Managers will be careful in making decisions because it will affect the manager, namely the manager's excellent name, so he will try his best to make the right decisions for the company's welfare (Septiadi et al, 2017). In this case, managers have the opportunity to use tax aggressiveness strategies to increase their bonuses and dividends.…”
Section: Resultsmentioning
confidence: 99%
“…Berdasarkan teori pemangku kepentingan, perusahaan bertanggung jawab bukan hanya kepada investor, melainkan juga kepada pemerintah, kreditor, karyawan, pemasok, dan konsumen (Firmansyah & Estutik, 2020). Mulyani et al (2017), Rahmawati et al (2016) dan Septiadi et al (2017) menyimpulkan bahwa penerapan tanggung jawab sosial perusahaan dapat menurunkan aktivitas penghindaran pajak. Sementara itu, Firmansyah & Estutik (2020) menyimpulkan bahwa tanggung jawab sosial dapat menurunkan tindakan penghindaran pajak yang dilakukan secara agresif.…”
Section: Kerangka Teoriunclassified